2022
DOI: 10.1371/journal.pone.0263514
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a credit-bearing online administered happiness course on undergraduates’ mental well-being during the COVID-19 pandemic

Abstract: Psychoeducational courses focused on positive psychology interventions have been shown to benefit student well-being. However, since the onset of the COVID-19 pandemic and accompanying social restrictions, many educators have had to deliver their courses online. Given that online teaching presents a very different university experience for students, do psychoeducational courses provide similar well-being benefits in an online format? In this pre-registered study (https://osf.io/3f89m), we demonstrate that desp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 54 publications
1
30
0
Order By: Relevance
“…Hood et al (2021) also showed positive effects in mental wellbeing, life satisfaction and lower loneliness, including during online "pandemic" versions. Likewise, Yale's 'Science of Well-Being' also evidenced greater subjective wellbeing (Yaden et al, 2021), while the latest study to be released (Hobbs et al, 2022) showed much the same.…”
Section: Positive Psychology In Higher Educationmentioning
confidence: 90%
See 4 more Smart Citations
“…Hood et al (2021) also showed positive effects in mental wellbeing, life satisfaction and lower loneliness, including during online "pandemic" versions. Likewise, Yale's 'Science of Well-Being' also evidenced greater subjective wellbeing (Yaden et al, 2021), while the latest study to be released (Hobbs et al, 2022) showed much the same.…”
Section: Positive Psychology In Higher Educationmentioning
confidence: 90%
“…warranted. Indeed, while Hobbs et al (2022) showed positive but small effects, they also noted that for-credit offerings are low-intensity tools for large groups, but not high-intensity tools for individuals in clinical settings where efficacy is expectedly higher.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations